INTERNALISASI NILAI-NILAI MODERASI BERAGAMA MELALUI PEMBELAJARAN PAI DI SEKOLAH MULTIKULTURAL: STUDI KASUS DI SMA NEGERI 17 TEBO - Yanti, Ely; Sabli, Muhammad; Kurniawan, Sugeng; Andryadi; Yulia Friska, Sonia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
Identity polarization and potential intolerance at the secondary school level demand the strengthening of religious moderation internalization as a foundation for national character. This study aimed to map the internalization process of religious moderation values through Islamic Religious Education (PAI) in a multicultural school context. A qualitative case study design was implemented at SMA Negeri 17 Tebo Regency involving four PAI teachers, 15 students from diverse cultural/religious backgrounds, one principal, and one community leader. Data were collected through in-depth interviews, participatory observation (4 months, 24 meetings), and policy/RPP document analysis. Thematic analysis revealed three internalization dimensions: cognitive (contextual understanding of religious texts & religious literacy), affective (empathy, teacher modeling, interfaith dialogue), and behavioral (cross-identity collaboration, peaceful conflict resolution, social participation). Findings indicate that internalization effectiveness depends on teachers’ pedagogical strategies integrating moral exemplarity, multicultural case-based learning, and explicit-hidden curriculum synergy. Key challenges include limited affective-behavioral assessment tools, parental resistance to interfaith dialogue, and insufficient teacher training in moderation-oriented instructional design. This study recommends developing structured internalization assessment rubrics, PAI modules contextualized to Tebo, and teacher training oriented toward contact pedagogy. The contribution lies in mapping the micro-process of religious moderation internalization in PAI and providing an operational framework adoptable by similar multicultural schools.